Evaluating solubility, aggregation and sorption of nanosilver particles and silver ions in soils - Geranmayeh Oromieh, Aidin (2011)
Engineered nanoparticles (ENPs) are used in so many different products. ENPs are released into different environmental compartments. Silver nanoparticle (AgNP) is one of the most used ENPs. AgNPs may cause damage to the environment due to their toxicity and wide exposure. In this thesis possible exposure ways of AgNPs to the environment was reported. Also sorption-solubility and aggregation of AgNPs and AgNO3 based on the different concentration of Ag and pH function in clayey and sandy soil was investigated.